Structural dynamics of the human Orai1 channel revealed by cryo-electron microscopy - Yiming Zhang; Yuan Wang; Jindou Liu; Weiwei Bei; Hongkun Wang; Junli Wang; Lei Chen; Youjun Wang (PLoS ONE, 2026)
The pore-forming Orai1 protein is an essential component of store-operated calcium entry (SOCE), a process vital to diverse cellular and physiological functions. Mutations in human Orai1 cause severe immunodeficiencies and myopathies, yet structural insights have remained largely elusive. To address this, we studied the structure of detergent-solubilized human Orai1 (hOrai1) by cryo-electron microscopy. While the overall resolution is moderate, the reconstructed map confirms a conserved hexameric architecture and enables assignment of transmembrane helices. We observed profound structural heterogeneity, with particles adopting both C6- and C2-symmetric conformations, indicative of dynamic rearrangements. This study establishes a framework for future structural and mechanistic studies of hOrai1.